SUPERVISION OF THE “PALEMBANG CERDAS” EDUCATION ASSISTANCE PROGRAM OF BAZNAS, PALEMBANG CITY, 2021–2023 - Mia Permata Sari; Amilda Amilda; Afriantoni Afriantoni (Jurnal Konseling Pendidikan Islam, 2026)
Education is a fundamental right for every citizen and a crucial factor in human development. To broaden learning access for children from low‑income families, BAZNAS of Palembang City launched the “Palembang Cerdas” education assistance program. This study evaluates the program’s implementation effectiveness, its oversight mechanisms, and the challenges encountered during the 2021‑2023 period. The methodology includes literature review, field observation, in‑depth interviews with beneficiaries and BAZNAS officials, and analysis of administrative documents. Findings show that applying the principles of right targeting, right purpose, right quantity, right timing, and right administration enhanced transparency and accountability in the allocation of zakat, infaq, and sadaqah funds, resulting in a significant increase in scholarships disbursed and a reduction of educational disparity in Palembang. However, three major obstacles were identified: (1) limited human resources, (2) an administrative system that is not yet fully digitized, and (3) sub‑optimal inter‑institutional coordination. Recommendations include strengthening human‑resource capacity through specialized training, implementing a real‑time, dashboard‑driven information system, and deepening collaboration with local government, educational institutions, and the private sector. Implementing these suggestions is expected to not only improve the quality and equity of education in Palembang but also position “Palembang Cerdas” as a replicable model for similar education assistance programs nationwide.